Understanding Collective Historical Trauma in Protracted Social Conflicts - Yassine, Fayza (2023)
This thesis examines the impact of collective historical trauma on the resolution of protracted social conflicts, with a specific focus on Lebanon's post-civil war period. By exploring the effectiveness of post-conflict strategies and the absence of a trauma-sensitive approach by the state, the study aims to emphasize the significance of adopting a comprehensive and trauma-sensitive approach to conflict resolution. Through an analysis of the government's conflict resolution approach and an investigation of initiatives introduced by governmental and non-governmental entities to address past conflicts, this study sheds light on the complexities of post-conflict dynamics in Lebanon. Central to the thesis is the recognition of collective historical trauma as a crucial component in conflict resolution. It argues that a trauma-sensitive approach should encompass the psycho-social effects of past conflicts, as well as structural and cultural violence. Importantly, the study highlights the need to move away from communal memory, as the fragmentation of memory into communal groups perpetuates divisive memory cultures and poses significant risks of future conflicts. By addressing the underlying fears and transmitted traumas embedded in current communal memories and cultures, the thesis argues that it becomes possible to break free from the cycle of violence and address the structural deficiencies that perpetuate conflict. The study aims to contribute to the development of effective and inclusive post-conflict strategies that prioritize the mental and emotional well-being of the Lebanese people. Through its comprehensive analysis and nuanced exploration, this thesis seeks to provide valuable insights into the complexities of post-conflict societies, emphasizing the importance of trauma-sensitive approaches and inclusive strategies for sustainable peace building.